(untitled) (Bangladesh Journal of Medical Science, 2013)
Introduction: Caesarean section (CS) is one of the most common surgical interventions to ensure safe delivery and outcome. Cost of CS is comparatively higher in private hospitals but it is not verified that this higher cost could influence the better outcome in private over a public hospital. Objectives: To compare cost and outcome of caesarean section between a public and private hospital. Materials and Methods: This cross-sectional comparative study was carried out among 130 clients of CS from Dhaka Medical College Hospital (DMCH) and Holly Family Red Crescent Hospital (HFRCH). Data were collected by face-to-face interview and reviewing medical documents. Cost of CS was estimated in terms of direct and indirect cost of CS incurred by the women while outcome was assessed by finding the health condition of the mother and newborn. Result: Majority of the women had CS as per doctor’s advice. Majority (61.5%) had different kind of problems after CS including lower abdominal pain (86.0% in HFRCH and 69.2% in DMCH) and fever (10.7% in HFRCH and 17.3% in DMCH). Average cost of CS was significantly higher in HFRCH (Tk.36852.90±8396.38) than in DMCH (Tk.7344.23± 5081.67) [t(128), p<0.01]. Both direct and indirect cost of CS were significantly lower in DMCH than in HFRCH [t(128), p<0.01]. Outcome of CS was significantly better to mothers in DMCH than of HFRCH [?2 (7.9)=0.048, p<.05]. Conclusion: Cost of CS was higher in private hospital while outcome was better in public hospital. Effective measures are recommended for reduction of cost of CS to make it cost-effective. Bangladesh Journal of Medical Science Vol. 12 No. 03 July 13 Page 276-281 DOI: http://dx.doi.org/10.3329/bjms.v12i3.15424